Cultural Tradition and Wildlife Conservation in the Human-Dominated Landscape of Rural Western Rajasthan, India - Hall, Jonathan C.; Chhangani, Anil K. (Indian Forester, 2015)
An investigation was carried out regarding the role of the Bishnoi people’s protection blackbuck antelope for conservation of this threatened species by testing the prediction that villages with Bishnoi have more blackbuck than villages without Bishnoi. There was significantly more blackbuck in villages with Bishnoi despite no significant difference in available habitat or human population between village classes. It was estimated that blackbuck occupied approximately one-third of total habitat and had high overall persistence over a four year period. This study provides evidence that Bishnoi lands can be important for blackbuck conservation and, more broadly, evidence that cultural traditions are important for conservation in human-dominated landscapes.